2018
DOI: 10.1111/bcp.13562
|View full text |Cite
|
Sign up to set email alerts
|

Clinical safety, tolerability, pharmacokinetics and effects on urinary electrolyte excretion of AZD9977, a novel, selective mineralocorticoid receptor modulator

Abstract: The results in man contradict the results in rodent models driven by aldosterone, in which AZD9977 has minimal electrolyte effects. Future clinical studies with AZD9977 should be performed in presence of endogenous or exogenous aldosterone to assess potential benefit of AZD9977 in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…The aldosterone response to AZD9977 supports target engagement, and the lack of effect on electrolytes is consistent with its hypothesized mechanism of action. The study confirmed the safety profile and pharmacodynamic effects of AZD9977 observed in a previous single‐dose phase I study in healthy volunteers . The results of these studies suggest that AZD9977 may protect against aldosterone‐mediated organ damage, with a reduced risk of hyperkalemia compared with MR antagonists.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The aldosterone response to AZD9977 supports target engagement, and the lack of effect on electrolytes is consistent with its hypothesized mechanism of action. The study confirmed the safety profile and pharmacodynamic effects of AZD9977 observed in a previous single‐dose phase I study in healthy volunteers . The results of these studies suggest that AZD9977 may protect against aldosterone‐mediated organ damage, with a reduced risk of hyperkalemia compared with MR antagonists.…”
Section: Discussionsupporting
confidence: 83%
“…Additional support for this explanation is the similar dose proportionality in exposure on day 1 and day 8, the time needed to reach steady‐state, and the stable morning and evening C trough levels at steady‐state. Moreover, regional absorption of AZD9977 was explored in a previous study and the extent of colonic absorption was reported to be sufficient for development of a controlled release formulation . AZD9977 did not increase 4β‐hydroxycholesterol levels, indicating no induction of CYP450 3A4/3A5.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations